Preconditioning of AISI 304 stainless steel surfaces in the presence of flavins—Part II: Effect on biofilm formation and microbially influenced corrosion processes. Issue 6 (8th December 2020) - Wurzler, Nina; Schutter, Jan D.; Wagner, Ralph; Dimper, Matthias; Hodoroaba, Vasile‐Dan; Lützenkirchen‐Hecht, Dirk; Ozcan, Ozlem
Abstract: Biofilm formation and microbially influenced corrosion of the iron‐reducing microorganism Shewanella putrefaciens were investigated on stainless steel surfaces preconditioned in the absence and presence of flavin molecules by means of XANES (X‐ray absorption near‐edge structure) analysis and electrochemical methods. The results indicate that biofilm formation was promoted on samples preconditioned in electrolytes containing minute amounts of flavins. On the basis of the XANES results, the corrosion processes are controlled by the iron‐rich outer layer of the passive film. Biofilm formation resulted in a cathodic shift of the open circuit potential and a protective effect in terms of pitting corrosion. The samples preconditioned in the absence of flavins have shown delayed pitting and the samples preconditioned in the presence of flavins did not show any pitting in a window of −0.3‐ to +0.0‐V overpotential in the bacterial medium. The results indicate that changes in the passive film chemistry induced by the presence of minute amounts of flavins during a mild anodic polarization can change the susceptibility of stainless steel surfaces to microbially influenced corrosion. Abstract : The presence of flavins during preconditioning alters the passive film chemistry and microbially influenced corrosion processes on AISI 304 stainless steels